Time-restricted eating for prevention of age-related vascular cognitive decline in older adults: A protocol for a single-arm open-label interventional trial. - Ana Clara da C Pinaffi-Langley; Zsofia Szarvas; Anna Peterfi; Zalan Kaposzta; Peter Mukli; Ali Shahriari; Mihaly Muranyi; Camila B Pinto; Cameron D Owens; Cheryl Adams; Brittany Karfonta; Michael Rohan; et al. (PLoS ONE)
Age-related cerebromicrovascular endothelial dysfunction underlies the initiation and progression of cognitive dysfunction and dementia, thus increasing the susceptibility of older adults to such conditions. Normal brain function requires dynamic adjustment of cerebral blood flow to meet the energetic demands of active neurons, which is achieved the homeostatic mechanism neurovascular coupling (NVC). In this context, therapeutical strategies aimed at rescuing or preserving NVC responses can delay the incidence or mitigate the severity of age-related cognitive dysfunction, and time-restricted eating (TRE) is a potential candidate for such a strategy. Studies have reported that TRE can improve cardiometabolic risk factors in older adults. However, the effect of TRE on cerebrovascular endothelial function remains unexplored. Thus, this protocol outlines the study procedures to test our hypothesis that a 6-month TRE regimen of 10-h eating window will improve NVC responses and endothelial function in community-dwelling older adults. This is a single-arm, open-label interventional trial. We aim to recruit 32 adults aged 55-80 years. Participants are instructed to maintain a TRE regimen of 10 h of free eating followed by 14 h of fasting for 6 months. Before and after fasting, participants are assessed for cognitive performance, peripheral micro- and macrovascular endothelial function, and NVC responses, as well as for several confounding factors, including body composition, dietary, and physical activity data. We expect that 6 months of TRE will improve NVC response and endothelial function in older adults compared with baseline, and that these improvements will be accompanied by improvements in cognitive performance. The study proposed herein will provide critical insight into a new potential therapeutical strategy for targeting age-related cognitive dysfunction. Ultimately, slowing down or alleviating cognitive decline will translate into improved quality of life and longer healthspan for aging adults. This study was prospectively registered at ClinicalTrials.gov (NCT06019195) on August 24, 2023.